Grain orientation dependence of deformation microstructure evolution and mechanical properties in face-centered cubic high/medium entropy alloys. Issue 1 (1st July 2022) - Yoshida, S; Fu, R; Gong, W; Ikeuchi, T; Bai, Y; Feng, Z; Wu, G; Shibata, A; Hansen, N; Huang, X; Tsuji, N
Abstract: This study revealed characteristics of the deformation behavior in high/medium entropy alloys (HEAs/MEAs) with face-centered cubic (FCC) structure. A Co60 Ni40 alloy and a Co20 Cr40 Ni40 MEA having low and high friction stresses (fundamental resistance to dislocation glide in solid solutions), respectively, but similar in other properties, including their stacking fault energy and grain sizes, were compared. The MEA exhibited a higher yield strength and work-hardening ability than those in the Co60 Ni40 alloy at room temperature. Deformation microstructures of the Co60 Ni40 alloy were composed of coarse dislocation cells (DCs) in most grains, and a few deformation twins (DTs) formed in grains with tensile axis (TA) nearly parallel to <111>. In the MEA, three microstructure types were found depending on the grain orientations: (1) fine DCs developed in TA //<100>-oriented grains; (2) planar dislocation structures (PDSs) formed in grains with other orientations; and (3) dense DTs adding to the PDSs developed in TA //<111>-oriented grains. The results imply difficulty in cross-slip of screw dislocations and dynamic recovery in the MEA, leading to an increase in the dislocation density and work-hardening rate. Our results suggest that FCC high-alloy systems with high friction stress inherently develop characteristic deformation microstructures advantageous for achieving high strength and large ductility.